SIMPANAN KARBON PADANG LAMUN DI KAWASAN PANTAI SANUR, KOTA DENPASAR - Yoga Ibnu Graha; I Wayan Arthana; I Wayan Gede Astawa Karang (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2016)
Seagrass is one of the marine resources that considerably potential as a CO2 absorbent and functioned as carbon sinks in the oceans known as blue carbon. The result of carbon sequestration from the process of photosynthesis is stored as carbon stocks on seagrass tissue, or streamed to multiple compartments, such as sediment, herbivores and other ecosystems. This study aims to assess the potential for carbon stock storage in biomass on a tissue of seagrass in Sanur Beach coastal area. The observations of seagrass are included the seagrass type, seagrass stands, and measurement of environmental parameters. Then the sampling was conducted to obtain the value of seagrass biomass. The carbon stocks obtained through the conversion of biomass by using carbon concentration analysis of seagrass tissue and then carried a spatial distribution of carbon stocks. Types of seagrass found in Sanur Beach coastal area consist of eight species that are Enhalus acroides, Thalassia hemprichii, Halophila ovalis, Syringodium isoetifolium, Cymodocea serrulata, Cymodocea rotundata, Halodule uninervis and Halodule pinifolia. The result of the carbon stock seagrass in the bottom substrate is 60% greater than the carbon stock in the top substrate which is 40%. Seagrass covering 322 ha of Sanur Beach coastal area with a total potential carbon storage of 66.60 tons or 0.21 tons / ha. Seagrass key role as a carbon storage is on the bottom substrate tissue, and Enhalus acroides is a seagrass species that contributes the most to the carbon storage.